Prevalence of Metabolic Syndrome One Year after Delivery in Finnish Women at Increased Risk for Gestational Diabetes Mellitus during Pregnancy - Jatta Puhkala; Tarja I. Kinnunen; Tommi Vasankari; Katriina Kukkonen-Harjula; Jani Raitanen; Riitta Luoto (Journal of Pregnancy)
Background. Women with a history of gestational diabetes mellitus (GDM) are at increased risk for metabolic syndrome (MeS) after delivery. We studied the prevalence of MeS at one year postpartum among Finnish women who in early pregnancy were at increased risk of developing GDM. Methods. This follow-up study is a part of a GDM prevention trial. At one year postpartum, 150 women (mean age 33.1 years, BMI 27.2 kg/m2) were evaluated for MeS. Results. The prevalence of MeS was 18% according tothe International Diabetes Federation(IDF) criteria and 16% according toNational Cholestrol Education Program(NCEP) criteria. Of MeS components, 74% of participants had an increased waist circumference (≥80 cm). Twenty-seven percent had elevated fasting plasma glucose (≥5.6 mmol/L), and 29% had reduced HDL cholesterol (≤1.3 mmol/L). The odds ratio for the occurrence of MeS at one year postpartum was 3.0 (95% CI 1.0–9.2) in those who were overweight before pregnancy compared to normal weight women. Conclusions. Nearly one-fifth of the women with an increased risk of GDM in early pregnancy fulfilled the criteria of MeS at one year postpartum. The most important factor associated with MeS was prepregnancy overweight. Weight management before and during pregnancy is important for preventing MeS after delivery.